Treponema denticola induces actin rearrangement and detachment of human gingival fibroblasts. - Baehni, P C (1992)
Spirochetes are associated with destructive periodontal diseases, and one cultivatable oral species, Treponema denticola, binds to mammalian cells and perturbs metabolism. To evaluate the cytoskeletal responses and attachment functions of human gingival fibroblasts (HGF) exposed to T. denticola, monolayers of HGF were incubated with T. denticola strains ATCC 35405, e, and e' in serum-free medium. HGF retracted pseudopods, rounded up, and ultimately detached from the substratum. Scanning electron microscopy showed spirochetes in close contact with HGF surfaces; occasionally, bacteria were partially submerged between folds in the HGF membrane. Blebbing and numerous microvilli formed on the cell surface as the HGF retracted. By confocal microscopy, spirochetes were detected in contact with the HGF surface but were never found on the ventral surface of fibroblasts between the substratum and cell. Morphological alterations were associated with and preceded by actin assembly, as measured by microscopic fluorimetry: there was a 263% increase in actin fluorescence over controls within 30 min. Detachment of fibroblasts from the substratum was related to incubation time and was dependent on the concentration of T. denticola. Detachment was observed for all strains tested and was also dependent on the viability of T. denticola: UV light, heat, and metronidazole treatment markedly reduced the HGF detachment response. Detachment was also significantly reduced by the protease inhibitor phenylmethylsulfonyl fluoride. HGF viability was not significantly affected by coincubation with spirochetes, as measured by lactate dehydrogenase release. Thus, T. denticola induces rapid cytoskeletal remodelling followed by cell detachment, which might be stimulated by a bacterially associated protease but is not likely directly mediated by proteolytic degradation at the cell-substratum adhesive contact points.